Diagnostic value of exosomal circMYC in radioresistant nasopharyngeal carcinoma. Issue 12 (18th September 2020) - Luo, Yanwei; Ma, Jinqi; Liu, Fengxia; Guo, Jie; Gui, Rong
Abstract: Background: The relationship between circulating exosomal circular RNA (circRNA) and prognosis of patients with nasopharyngeal carcinoma (NPC) remain unknown. This study focused on the expression of exosomal circMYC and its relationship with the recurrence and prognosis of patients with NPC. Methods: The circulating exosomes were obtained from 210 patients with NPC. Quantitative polymerase chain reaction, 5‐ethynyl‐2′‐deoxyuridine (EdU) staining, colony formation, and bioinformatic analysis were performed. Results: Circulating exosomal circMYC was significantly increased in patients with NPC and was associated with tumor size, lymph node metastasis, TNM stage, survival rate, and disease recurrence. Gain‐functional and loss‐functional experiments revealed that overexpression of circMYC promoted cell proliferation and reduce radiosensitivity, while knockdown of circMYC inhibited cell proliferation and enhanced radiotherapy. Conclusion: circMYC is an oncogene in NPC cells and can enhance the radiotherapy resistance of NPC cells. Circulating exosomal circMYC can be used as a potential therapeutic target for NPC.